Fifteen-day cessation of training on selected physiological and performance variables in women runners - Doherty, R. A.; Neary, J. P.; Bhambhani, Y. N.; Wenger, H. (The Journal of Strength and Conditioning Research, 2003)
This study examined the effects of a 15-day cessation of training on maximal oxygen consumption and selected physiological variables (maximal heart rate, cardiac output [Q], stroke volume [SV], arteriovenous oxygen difference [(a-v)O2 diff], blood plasma concentration) in 15 women middle-distance competitive runners (O2max: 49.8 ± 1.1 ml·kg1·min1). Subjects were randomly assigned to a cessation training (CT, n = 7) or maintenance training (MT, n = 8) group and tested every 5 days. Q was measured by CO2 rebreathing from which SV and (a-v)O2 diff were calculated. No significant changes were found at day 5. After 10 days there was a significant decrement in O2max (3.8 ml·kg1·min1) in the CT group, being significantly lower than MT but no changes thereafter in any physiological variables. Performance (2,400 m) times did not change for MT but was significantly slower (21.5 ± 7.1 seconds) for the CT group after 15 days, corresponding to the 7.8% decrease in O2max. These findings suggest that in competitive women middle-distance runners, actual performance decrements found after 15 days of CT most likely are due to declines in O2max.